Profiling the rapist: a study on rapists in the Seremban, Johor Bahru, Kajang and Sungai Buloh prisons / Rachel Samuel, Prof. Madya Dr. Rohana Ariffin and Sujatha Menon - Samuel, Rachel; Ariffin, Prof. Madya Dr. Rohana; Menon, Sujatha (Pusat Penerbitan Universiti (UPENA), 2005)
The number of rape incidents in the country is showing an increasing trend. It is reported that an average of four women get raped everyday in Malaysia. As the rapists are the perpetrators of the crime, it is hoped that an insight into their thoughts, feelings, perception and attitude would help reduce the number of rape incidents in our country. The objectives of the study are obtaining a socio-economic profile of the rapists, understanding the family background of the rapists and outlining programmes which can help combat the rise of rape incidents. This study outlines the profile of the Malaysian rapists. A total of 90 convicted rapists from Seremban, Johor Bahru, Kajang and Sungai Buloh prisons were interviewed. Majority of the offenders were Malay and were aged between 45 to 55 years old. The most common types of rape were incest and acquaintance rape. The victims were mainly 16 years and below. The Malaysian rapist originates mainy from the rural areas and has low education. They are mainly married. Most of them reported good relationship with their mothers but not their fathers. Their views concerning females in general were degrading and humiliating. These views affected their overall perception and attitudes towards women. Though rape is a violent crime, the responses from the convicted rapists show that they see rape as a sexual act.